Penggunaan Video Animasi pada Sistem Kopling Manual untuk Meningkatkan Minat dan Hasil Belajar Siswa (Lembag, 2026)
This study aims to examine the implementation of animated video media on manual clutch systems to improve students’ learning interest and learning outcomes in the power transmission system material at SMK Muhammadiyah Sadang. This research employed Classroom Action Research (CAR) consisting of planning, acting, observing, and reflecting stages. The subjects of the study were 25 students of class XI TKR. The instruments used included lesson plans, learning materials, student interest questionnaires, and learning outcome tests. The results showed a significant improvement in both learning interest and learning outcomes after the implementation of animated video media. Students’ learning interest increased from 71% in the initial condition to 80.2% in the second cycle. Meanwhile, learning mastery improved from 36% in the pre-action stage to 72% in the first cycle and reached 84% in the second cycle. The continuous improvement across cycles indicates that the use of animated video media effectively enhances student engagement and academic achievement. Therefore, animated video media can be considered an effective instructional strategy in vocational education, particularly in automotive engineering learning.